80.7k views
0 votes
Need answer ASAP plz

Need answer ASAP plz-example-1
User ThanaDaray
by
5.1k points

2 Answers

3 votes

Answer:

Choice C is correct.

Explanation:

We have given the equation:

(x+1)(x-3)=5

We have to choice the correct option.

Product property states that:

if ab=0 then a=0 or b =0.

(x+1)(x-3)=5

x²-2x-3 = 5

x²-2x-3-5 = 0

x²-2x-8 = 0

factorize the above equation we get,

x²+2x-4x-8=0

x(x+2)-4(x+2) = 0

(x+2)(x-4) = 0

Using zero product property we get,

(x+2) = 0 or (x-4) = 0

So, choice C is correct.

User Chrset
by
5.2k points
4 votes

ANSWER


x - 4 = 0 \: or \: x + 2 = 0

EXPLANATION

Given:


(x + 1)(x - 3) = 5

Expand:


{x}^(2) - 3x + x - 3 = 5


{x}^(2) - 2x - 3 = 5

Equate everything to zero.


{x}^(2) - 2x - 3 - 5 = 0


{x}^(2) - 2x - 8 = 0

Split the middle term;


{x}^(2) + 2x - 4x - 8 = 0

Factor;


x(x + 2) - 4(x + 2) = 0


(x - 4)(x + 2) = 0

Use zero product property,


x - 4 = 0 \: or \: x + 2 = 0

User WiatroBosy
by
5.1k points